Studi Kasus Perlindungan Sosial Melalui PKH, BLT, dan BSU: Upaya Mengurangi Ketergantungan Pinjaman pada Masyarakat Rentan di Kota Jambi - Indra Yudha, Redi; Hakim, Lukman; Sabandi, Muhammad (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to understand in depth how social protection programs in the form of the Family Hope Program (PKH), Direct Cash Assistance (BLT), and Wage Subsidy Assistance (BSU) are implemented as social security instruments for underprivileged communities in Jambi City, particularly in an effort to reduce their dependence on informal lending practices and high-interest loans. Referring to Campbell's descriptive qualitative research method approach, this study emphasizes the narrative and contextual depiction of phenomena through case studies. Data were collected through in-depth interviews with beneficiaries, village officials, and social assistance officers in three sub-districts with the highest poverty rates in Jambi City. The results show that the existence of the PKH, BLT, and BSU programs has provided tangible benefits in meeting basic household needs, especially food and children's education. This has resulted in a decrease in the frequency of vulnerable communities taking out high-interest loans, which are generally intended to cover urgent consumption needs.